2014
DOI: 10.4085/1062-6050-49.3.86
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Instrumented Measurements of Hip Laxity and Their Associations With Knee Laxity and General Joint Laxity

Abstract: Context: Hip-joint laxity may be a relevant anterior cruciate ligament injury risk factor. With no devices currently available to measure hip laxity, it is important to determine if clinical measurements sufficiently capture passive displacement of the hip.Objective: To examine agreement between hip internalexternal-rotation range of motion measured clinically (HIER ROM ) versus internal-external-rotation laxity measured at a fixed load (HIER LAX ) and to determine their relationships with knee laxity (anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For instance, greater ROM TOT has been associated with generalized joint laxity (r ¼ 0.57), 10 a prospectively identified ACL injury risk factor in females. 11 Although passive hip ROM during functional activity has been empirically linked to dynamic knee valgus during functional activity 6,12 and females have been reported to differ from males in passive hip ROM, 10 literature quantifying normative ranges of motion by sex is lacking. This gap can be particularly problematic considering that females may exhibit different injury mechanisms than males.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, greater ROM TOT has been associated with generalized joint laxity (r ¼ 0.57), 10 a prospectively identified ACL injury risk factor in females. 11 Although passive hip ROM during functional activity has been empirically linked to dynamic knee valgus during functional activity 6,12 and females have been reported to differ from males in passive hip ROM, 10 literature quantifying normative ranges of motion by sex is lacking. This gap can be particularly problematic considering that females may exhibit different injury mechanisms than males.…”
mentioning
confidence: 99%
“…3 Previous reports of transverse-plane hip ROM values are presented in Table 1. Researchers who examined sex differences in ROM IR and ROM ER have suggested that females possess more ROM IR than ROM ER and more ROM IR than males in a healthy population 10 and elite tennis players. 16 However, as a result of the limited data on athletic populations, these sex comparisons may not be generalizable to individuals participating across a variety of sports.…”
mentioning
confidence: 99%
“…Compared with males, females likely display greater dynamic knee valgus during those activities [9]. Females differ from males in passive hip ROM [14]. Ranges of hip IR and external rotation (ER) are highly correlated with radiographic measures of femoral anteversion [15].…”
Section: Dynamic Knee Valgus Comprises Hip Internal Rotation (Ir)mentioning
confidence: 99%
“…[10][11][12] Femoral anteversion is characterized by a medially-torsioned femoral neck and is developmental. 13 In contrast, passive hip RoM is a pliable soft tissue restraint which may be influenced by other factors such as general joint laxity, 14 that has been shown to remain constant throughout maturation, 15 and has been retrospectively associated with ACL injury. 16 Though these factors cannot be directly modified through training interventions, it may be possible to design more effective intervention strategies to counteract non-modifiable anatomical factors.…”
mentioning
confidence: 99%